Faktor – Faktor yang Mempengaruhi Perilaku Konsumtif Generasi Z pada Penggunaan Jasa Layanan Antar Makanan : Studi Kasus Kecamatan Percut Sei Tuan - Silvia Anjani Nasution; Sugianto Sugianto; Reni Ria Armayani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the factors that influence the consumer behavior of generation z towards the use of food delivery services in Percut Sei Tuan District. The methodology used in this study is the quantitative method. The independent variables in this study are perceptions of convenience, perceptions of usefulness, and religiosity. While the dependent variable is consumer behavior. The sampling technique in this study was the purposive sampling technique, which took respondents who were generation z aged between 15-24 as many as 100 respondents. The influence of perceptions of convenience, perceptions of usefulness, and religiosity contributed 58% to consumer behavior, the remaining 42% was explained by other variables outside this study. The results of the t-test concluded that the variables of perceptions of convenience and usefulness had a positive and significant effect on the consumer behavior of generation z in the use of food delivery services, while the variable of religiosity did not have a significant effect on the consumer behavior of generation z in the use of food delivery services in Percut Sei Tuan District. Based on the ANOVA test, the f-count obtained was 46.488, which is greater than the f-table, which is (2.699), it is concluded that the perception of convenience, perception of usefulness, and religiosity have a simultaneous effect on the consumer behavior of generation z towards the use of food delivery services in Percut Sei Tuan District.